The Potential of Habbatussauda (Nigella sativa) Effervescent Tablet Extract as a Denture Cleanser against the Growth Inhibition of Staphylococcus aureus on Acrylic Resin Plates - Faizah, Ariyani; Rochmanita Suparno , Nilasary; Mahaningrum, Gunasti; Marsetyawan Dani Artha, Antony (Jurnal Kesehatan Gigi, 2025)
Chemical cleaning of dentures using a denture cleanser is essential to prevent denture stomatitis—an infection of the oral mucosa caused by bacteria such as Staphylococcus aureus adhering to the denture base. One key component of denture cleansers is an antibacterial agent. Habbatussauda (Nigella sativa) contains antibacterial compounds that may serve as an alternative active ingredient in denture cleansers. This study aimed to evaluate the potential of effervescent tablets containing Habbatussauda extract as a denture cleanser in inhibiting Staphylococcus aureus growth on acrylic resin denture bases. The study employed a true experimental, post-test-only control group design, using 24 acrylic resin plates divided into six treatment groups: Habbatussauda extract concentrations of 9%, 12%, 15%, and 18%, along with positive and negative controls. Each plate was immersed in the respective Habbatussauda-based denture cleanser solution for 15 minutes. Researchers then counted the bacterial colonies using a colony counter. The Kruskal-Wallis test yielded a significant difference in colony counts (p < 0.05). Post hoc analysis with Bonferroni correction revealed significant differences between the 12% and 18% extract groups, as well as the positive control, compared to the negative control. However, no significant differences emerged between the extract groups (9%, 12%, 15%, and 18%) and the positive control. These findings indicate that Habbatussauda extract-based denture cleansers effectively inhibit Staphylococcus aureus growth on acrylic resin denture bases after 15 minutes of immersion.